PROFESSIONAL TRAINING OF FUTURE TEACHERS IN THE REPUBLIC OF POLAND: COMPETENCE APPROACH (Educological discourse, 2015)
The article deals with professional competences, which should master future teachers in the Republic of Poland; it analyses the groups of professional competences according to the standard of professional competences of the teachers of the modern Polish school; it describes the basic competences of the Polish school teacher, highlighting by the national and the Polish scientists; it focuses on sociocultural competence of future teachers and the need of information technology education of teachers of all directions of training; the article deals with the problem of raising the professional competence of future teachers.